Maternal Healthcare in Low- and Middle-Income Countries: A Scoping Review - Sena Belina Kitila; Garumma Tolu Feyissa; Alemi Kebede Olika; Muluemebet Abera Wordofa (SAGE Publishing, 2022)
Background: Continuum of care [COC] for maternal health care [MHC] refers to continuity of care that has been considered as a core principle and framework to underpin strategies and programs to save the lives and promote wellbeing of mothers and newborns. However, the status of the continuum of care for maternal health care is not well studied. Thus, the objective of this analysis is to examine the status of the continuum of care for maternal health care and current recommendations in Low- and Middle-Income Countries. Methods: Our review followed the scoping review methods. We searched for relevant studies in the PubMed, and Cochrane Library databases. Additionally, lateral searching was carried out from google scholar, reference lists of the included studies and supplemented by a gray literature search. One reviewer screened the full list, which was randomly split into two halves and independently screened by other 2 reviewers. The 2 reviewers independently extracted the data and discrepancies were resolved through discussion. Results: A total of 1259 records were identified through the databases and others searching strategies. Of these, 13 studies were included in the review and the year of their publication was from 2015 to 2019, more than half (53.8 %) of the included studies were from African countries. As to the source of data 53.8% of them were from countries' Demographic Health Survey [DHS], and all of them were cross sectional study by design. The general picture shows a decline in use of the services as women move along the continuum of care from pregnancy to childbirth and postnatal, and the highest gap was noticed between institutional delivery and postnatal care. The completion status differs from country to country and 60% in Cambodia during the 2010 CDHS but, 5% in Ratanakiri, Cambodia in 2015. Conclusion and recommendations: The status of continuum of care for maternal health care is varies across the countries. Also, there is limited studies on the continuum of maternal health care and more than half of the studies on this area were from countries' Demographic Health Survey and all of them were cross sectional by design. Furthermore, none of the reviewed studies considered status of continuum of care and birth outcomes. Hence, it is decisive to estimate the status of completion of continuum of care, completion, and its effect on birth outcomes in countries like Ethiopia where the burden of maternal and newborn mortality is high. Plain English summary Continuum of care for maternal health care means the continuity of care during prenatal, delivery and postnatal. It has been considered as core strategies to save the lives of mothers and newborns. We searched for relevant studies in the databases and gray literature. Two reviewers performed data extraction independently. A total of 1259 records were identified through searching. Thirteen studies were included in the review. More than half of the studies included were from African countries. Demographic Health Survey [DHS] reported from these countries formed the main source of data. All of them were cross sectional study by design. The general picture shows a decline in the use of the health services as women move along the continuum of care from ANC to PNC. The completion status varies across countries.